Design of Batch Distillation Columns Using Short-Cut Method at Constant Reflux - Asteria Narvaez-Garcia; Jose del Carmen Zavala-Loria; Luis Enrique Vilchis-Bravo; Jose Antonio Rocha-Uribe (Journal of Engineering)
A short-cut method for batch distillation columns working at constant reflux was applied to solve a problem of four components that needed to be separated and purified to a mole fraction of 0.97 or better. Distillation columns with 10, 20, 30, 40, and 50 theoretical stages were used; reflux ratio was varied between 2 and 20. Three quality indexes were used and compared: Luyben’s capacity factor, total annual cost, and annual profit. The best combinations of theoretical stages and reflux ratio were obtained for each method. It was found that the best combinations always required reflux ratios close to the minimum. Overall, annual profit was the best quality index, while the best combination was a distillation column with 30 stages, and reflux ratio’s of 2.0 for separation of benzene (i), 5.0 for the separation of toluene (ii), and 20 for the separation of ethylbenzene (iii) and purification of o-xylene (iv).